Effect of changes in the net height, court size, and serve limitations on technical-tactical, physical, and psychological aspects of U-14 female volleyball matches - Palao, Jose M.; Ureña, Aurelio; Moreno, Maria P.; Ortega-Toro, Enrique (Frontiers in Psychology, 2024)
Introduction The objective was to analyze the effect of a reduction of the net height and the court size and serve limitations on the technical-tactical actions, physical actions, and psychological aspects in youth volleyball players. Methods The sample was 29 under-14 female volleyball players (three regional club teams). A quasi-experimental design was implemented to assess the effect of modification in three tournaments. The independent variables were: a) official rules tournament (no changes in the rules), b) Experimental Tournament 1 (reduction in the net height from 2.10 m to 2 m, no jump serves, and a maximum of two serves per player and rotation), and c) Experimental Tournament 2 (reduction in net height from 2.10 m to 2 m, reduction in court size from 9 × 9 m to 8 × 8 m, no jump serves, and a maximum of two serves per player and rotation). The dependent variables were: ball contact done (type), quality and efficacy of the technical actions, team game phases occurrence, quality and efficacy, continuity index, number of jumps, player's jump load in the take-off and landing, number of hits, average heart rate, Rate of Perceived Effort, time between ball contacts, serve velocity, perceived individual and collective self-efficacy, perceived enjoyment, and perceived satisfaction. Results Experimental Tournament 1 involved an increase in the efficacy of serves and a decrease in the efficacy of side-out phases. The imbalance between serve and reception did not impact game continuity but reduced the attack and blocks. Experimental Tournament 2 involved a decrease in the efficacy of serves and an increase in the efficacy of side-out phases. The balance between serve and reception increased reception efficacy, the occurrence of attacks and blocks, game continuity, and players' effort. players' effort. Discussion Scaling the net and court and adapting the serve rules (Experimental Tournament 2) resulted in game dynamics for these U-12 teams that were more similar to those of posterior stages of player through the balance between serve and reception and the adaptation of the net height and court size.